HPLC of Hypericum perforatum Herb Cell Suspension Reveals Attractive Medical Flavanone Glycosides Compounds that are Supported by DFT Study - Taj Al-Deen, Aziza M.; Manaf, Hossam H.; Rizk, Sameh A. (PSM Biological Research, 2022)
In the present study, in vitro Hypericum perforatum leaves were used as a segment to induce callus culture. Callus morphogenesis was achieved using Murashige and Skoog’s culture media supplemented with different combinations of growth regulators. The best callus biomass was obtained with 0.22 mg/l (2,4-D) + 0.024 mg/l (Kin), and cell suspension culture succeeded in the production of new good circular cell biomass that was treated by three different stimulating compounds. The results showed that the best increase in the active ingredients was by chromone glycoside derivatives 2-5, as revealed via HPLC test of fractionation. The extracted H. perforatum L. was conveniently synthesized in 3 steps, from the commercially available Acetophloroglucine, which supported the extracted ingredients 2-5. The glucosyl moiety was introduced by stereoselective O-glycosylation with a per-O-benzylated glucosyl bromide donor, followed by the formation of the chalcone with debenzylation, which was carried out to afford 3 and 5 with overall yields of 64% and 73%, respectively. Finally, the density functional theory (DFT) was then applied to explore the structural and electronic characteristics of these materials. All the synthesized compounds have been characterized based on their 1H NMR, MS, and elemental analyses for the optimized precursors of the synthesized chromone glycosides.